Interview with Delores "Dee" Weaver - Klaffke, Lauren E.; Weaver, Delores "Dee" (University of Minnesota, 2013)
Delores Weaver begins her interview by elaborating on her education in South Dakota and then at the University of Minnesota. She then reflects on her military service in the Navy as part of the WAVES and her husband’s service in the Air Force. Mrs. Weaver then discusses her work as a flight attendant, her time doing procedure audits for Bechtel Company in San Francisco, and how she met her husband, Lawrence Weaver. She then reviews her husband’s early career, as an adjunct at Butler while working for Pitman-Moore, which became part of Dow Chemical, and his interest in pursuing a career in pharmacy. In reflecting on her husband’s work as dean of the College of Pharmacy at the University of Minnesota, Mrs. Weaver discusses all of the following regarding her husband’s work: the problems he faced with finding adequate space; creation of the PharmD program; the changing role of the pharmacist; his work on the formation of the Academic Health Center (AHC); lobbying the State Legislature; serving as vice president of professional relations for the Pharmaceutical Manufacturers of America (PMA); and his support of orphan drug work. She then discusses her own work as a volunteer at University Hospital, the couple’s return to the Twin Cities when Dr. Weaver served as temporary dean of the School of Pharmacy from 1994 to 1996, Dr. Weaver’s leadership style, and funding for the School. She concludes the interview by reviewing Dr. Weaver’s relationships with various vice presidents of the AHC and his work on orphan drugs.
Delores “Dee” Weaver was born and raised in South Dakota. She graduated from Lennox High School near Sioux Falls and then attended the University of Minnesota. She interrupted her education to serve in the Navy as part of the WAVES during World War II. She completed her service, and then continued work on her bachelor’s degree in business before pursuing a job as a flight attendant, based in Los Angeles. She then worked at Betchel Company in San Francisco as a procedural auditor until she married Lawrence Weaver and moved to Utah, where he was completing his Ph.D. in pharmacology at the University of Utah. In 1954, the Weavers moved to Indiana, where Dr. Weaver worked at Pitman-Moore, which became part of Dow Chemical, and served as an adjunct professor at Butler University and Indiana University. In 1966, the Weavers moved to Minnesota when Lawrence Weaver was offered the deanship of the College of Pharmacy at the University of Minnesota. During her time in Minnesota, Delores Weaver served as a volunteer at University Hospitals and Clinics while also raising the Weavers’ children. In 1984, Dr. Lawrence Weaver resigned from his position as dean to serve as vice president for professional relations for the Pharmaceutical Manufacturers of America (PMA) in Washington, D.C. He held this position until 1989. In 1994, the Weavers returned to Minnesota and the University, where Dr. Weaver served as interim dean until the hiring of Marilyn Speedie in 1996. As a result of Dr. Weaver’s work with the PMA, the Weavers became very involved in orphan drug advocacy, including Dr. Weaver’s cofounding of Orphan Medical, Inc., a company that develops therapies for the treatment of rare disorders. Dr. Lawrence Weaver died on December 21, 2011, but Mrs. Delores Weaver continues to live at their home in Fridley, MN.
Keywords: Academic Health Center; Health sciences; 1960s; 1970s; 1980s; 1990s; Pharm.D.; School of Dentistry